Motivasi Anggota Klub Maara Baca: Analisis Budaya Literasi Lokal di Kabupaten Jember - Maya Pradhipta Hapsari (Research Institute and Community Engagement of UIN MADURA, 2026)
Literacy plays an important role as a foundation for community development, because being â€œliterateâ€ is a capital to empower individuals, families, and communities in improving their quality of life. However, the challenge of low interest in reading in some communities is still an obstacle in strengthening literacy culture. This study aims to reveal the motivation of members of the Maara Baca Club in Jember Regency and their contribution to local literacy culture. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews with club members. The results of the study show that the Maara Baca Club, which was founded in November 2023, is a place for reading together that supports individual literacy habits and builds meaningful social networks. Members' motivations for joining include intrinsic motivation, namely a hobby of reading and a desire to increase insight, as well as extrinsic motivation, namely the influence of social media and the need to interact with new friends. This club contributes to strengthening local literacy culture through an inclusive and flexible approach, such as silent reading activities and reading challenges. In addition, the use of the name Maara Baca, which comes from the Madurese language, reflects Jember's local identity while strengthening cultural relevance in literacy activities. With an inclusive approach and supporting various groups, Maara Baca is able to increase participation in community literacy. This research provides insight into the importance of local culture-based communities in supporting the development of a collective literacy culture.